Desain Pelatihan Kewirausahaan Berbasis Digital untuk Akselerasi Graduasi Keluarga Penerima Manfaat Program Keluarga Harapan di Desa Rancakalong Sumedang - Nandyva, Alsha Frisma; Widiowati, Didiet (Jurnal Pengabdian Tri Bhakti, 2024)
The program that has been carried out by the PKH Facilitator of Rancakalong Village to reduce poverty is to hold a Family Capacity Building Meeting (P2K2) for KPM PKH, one of the materials discussed is financial management, but there has been no follow-up after the activity. So, a service was carried out in the form of entrepreneurship training aimed at mothers of PKH beneficiaries so that they could improve their family's economy through entrepreneurship so that it could help accelerate the graduation of KPM PKH. The targets of the training were 8 mothers of PKH beneficiaries who had the desire to become entrepreneurs. This program also uses digitalization for the monitoring and evaluation process. The steps taken consist of the dialog stage, the assessment and intervention plan stage, the intervention implementation and evaluation stage, as well as termination and referral.